Odpowiedzialność dyrektora za wyniki działalności przedsiębiorstwa - Kubot, Zdzisław (Wydział Prawa i Administracji UAM, 1988)
A manager of a state enterprise is subject to many different forms of responsibility. Among them an important place takes the responsibility for the effects of the economic activity of an enterprise. Responsibility for effects is indispensable in economic mechanisms based on competition. In the case of such mechanisms the main duty of a manager cannot be reduced to the obligation of due-diligence and a prerequisite of his/her responsibility cannot be reduced to guilt. The responsibility of managers of enterprises which report poor economic results or lose in competition with others should take the form of dismissal or financial sanctions (deprivai of bonuses and awards).
The manager's responsibility for the effects of the enterprise activity